2012
DOI: 10.1073/pnas.1209860109
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic membranes of the chloroplast in Chlamydomonas reinhardtii

Abstract: The polypeptide subunits of the photosynthetic electron transport complexes in plants and algae are encoded by two genomes. Nuclear genome-encoded subunits are synthesized in the cytoplasm by 80S ribosomes, imported across the chloroplast envelope, and assembled with the subunits that are encoded by the plastid genome. Plastid genome-encoded subunits are synthesized by 70S chloroplast ribosomes directly into membranes that are widely believed to belong to the photosynthetic thylakoid vesicles. However, in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 45 publications
3
38
0
Order By: Relevance
“…In such a case, they attract chaperones in the chloroplast, including BSD2, to prevent the formation of premature S-S bonds in the RbcL chain, which must refold after its translocation; however, in the absence of BSD2, the imported RbcL chains would not necessarily recapitulate the folding events that occur during the natural synthesis of the chloroplast-encoded RbcL. This premise is in line with the recent finding that subunits of photosynthetic complexes that are encoded by the nuclear and chloroplast genomes are translated on membrane-associated 'translation zones' that are located on both sides of the chloroplast envelope (Schottkowski et al, 2012).…”
Section: Discussionsupporting
confidence: 73%
“…In such a case, they attract chaperones in the chloroplast, including BSD2, to prevent the formation of premature S-S bonds in the RbcL chain, which must refold after its translocation; however, in the absence of BSD2, the imported RbcL chains would not necessarily recapitulate the folding events that occur during the natural synthesis of the chloroplast-encoded RbcL. This premise is in line with the recent finding that subunits of photosynthetic complexes that are encoded by the nuclear and chloroplast genomes are translated on membrane-associated 'translation zones' that are located on both sides of the chloroplast envelope (Schottkowski et al, 2012).…”
Section: Discussionsupporting
confidence: 73%
“…In situ assays in Chlamydomonas chloroplasts revealed that psbA mRNA is bound to thylakoid membranes via the nascent peptide during PSII repair, but is bound independent of translation to distinct "biogenic membranes" shortly after a dark-tolight shift (14,50). Our assays were performed 1 h into the light cycle on seedling leaf tissue at a stage with a young but assembled photosynthetic apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…We focused on the 8-oxoG immunofluorescence staining of the pyrenoid because it represents oxidized RNA and was atypical; we did not see this pattern for any of the four chloroplast mRNAs or nine chloroplast proteins that we analysed previously (not including RBCL and RBCS, which were seen in the pyrenoid) (Bohne et al, 2013;Schottkowski et al, 2012;Uniacke and Zerges, 2007, 2008). Therefore, 8-oxoG immunofluorescence staining of the pyrenoid represents the specific localization of oxidized RNA and is not due, for example, to nonspecific entry into the pyrenoid of RNA from the surrounding stroma (the chloroplast compartment analogous to the cytoplasm).…”
Section: Oxidized Rna Localizes Within the Pyrenoidmentioning
confidence: 99%